Iminoboronates as Dual‐Purpose Linkers in Chemical Probe Development. Issue 10 (14th January 2021) - van der Zouwen, Antonie J.; Jeucken, Aike; Steneker, Roy; Hohmann, Katharina F.; Lohse, Jonas; Slotboom, Dirk J.; Witte, Martin D.
Abstract: Chemical probes that covalently modify proteins of interest are powerful tools for the research of biological processes. Important in the design of a probe is the choice of reactive group that forms the covalent bond, as it decides the success of a probe. However, choosing the right reactive group is not a simple feat and methodologies for expedient screening of different groups are needed. We herein report a modular approach that allows easy coupling of a reactive group to a ligand. α‐Nucleophile ligands are combined with 2‐formylphenylboronic acid derived reactive groups to form iminoboronate probes that selectively label their target proteins. A transimination reaction on the labeled proteins with an α‐amino hydrazide provides further modification, for example to introduce a fluorophore. Abstract : Iminoboronate chemistry enables the synthesis of chemical probes that selectively label proteins of interest from 2‐formylphenylboronic acid reactive groups and hydrazide‐functionalized ligands. The reversibility of the iminoboronate linkage is exploited to detect the labeled proteins by ligand‐fluorophore exchange. Remarkably, the fast iminoboronate chemistry even allows probe formation within protein mixtures.